DO MOTION SIMULATION AND WHOLE BODY VIBRATION HAVE POSITIVE EFFECTS IN INSTITUTIONALIZED PATIENTS WITH DEMENTIA? - Heesterbeek, M (Innov Aging, 2018)
Pharmacological treatments to manage or cure dementia remain controversial. Therefore, development of non-pharmacological alternatives to delay the progression of dementia is urgently needed. Passive exercise (PE) is proposed to be such a non-pharmacological alternative and may be feasible for even the most vulnerable patients. This study aims to investigate the feasibility and effects of three different forms of PE on quality of life (QoL) and activities of daily living (ADLs) of institutionalized patients with dementia. Three forms of PE are distinguished; motion simulation (MSim), whole body vibration (WBV), and a combination of MSim + WBV. Intervention effects are compared to a control group receiving regular care. 112 Institutionalized patients with dementia (67.9% women, age 85.0 ± 7.2 years, MMSE 13.7 ± 6.4) followed a six-week intervention program consisting of four 4–12 minutes sessions a week. QoL and ADLs were assessed with validated questionnaires filled in by the formal caregiver of the participant. Cognitive and physical functions were assessed by individual testing. Given adherence rates of over 80% in all groups, an average experience score of 7,3 (on a scale from 0–10) and no observed adverse effects it was concluded that all three forms of PE were feasible to implement in this population. No significant effects of PE on QOL and ADLs, cognitive or physical function were found. Because of large day-to-day fluctuations and limited sensibility to detect change over time, collecting reliable data from this population remains challenging. Future implications and potential improvements for research in this population will be proposed during the session.